2015
DOI: 10.1016/j.ecoleng.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Fate of nitrate in seepage from a restored wetland receiving agricultural tailwater

Abstract: A B S T R A C TConstructed and restored wetlands are a common practice to filter agricultural runoff, which often contains high levels of pollutants, including nitrate. Seepage waters from wetlands have potential to contaminate groundwater. This study used soil and water monitoring and hydrologic and nitrogen mass balances to document the fate and transport of nitrate in seepage and surface waters from a restored flow-through wetland adjacent to the San Joaquin River, California. A 39% reduction in NO 3 -N con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Given that organic N usually has a shortterm retention potential in soil (McDowell, 2003), the subsurface movement of organic N from the SDA could be an important source of N to downstream waterbodies. Previous studies have suggested that during subsurface movement of N, a large part of the NO x -N is lost through denitrification under the anoxic conditions, thereby enhancing N treatment (Koron, 1992;Kliewer and Gilliam, 1995;Brauer et al, 2015). This is especially true for the warm, wet environment of the study area (Spalding and Exner, 1993).…”
Section: Nitrogen Dynamicsmentioning
confidence: 83%
“…Given that organic N usually has a shortterm retention potential in soil (McDowell, 2003), the subsurface movement of organic N from the SDA could be an important source of N to downstream waterbodies. Previous studies have suggested that during subsurface movement of N, a large part of the NO x -N is lost through denitrification under the anoxic conditions, thereby enhancing N treatment (Koron, 1992;Kliewer and Gilliam, 1995;Brauer et al, 2015). This is especially true for the warm, wet environment of the study area (Spalding and Exner, 1993).…”
Section: Nitrogen Dynamicsmentioning
confidence: 83%
“…Previous studies have revealed plant uptake, soil retention, denitrification, microbial immobilization and nitrification as the major process of nitrogen retention in wetlands [2426]. In wetlands which receive high nitrate loading from agricultural runoff or sewage treatment plant discharge, denitrification has been found as the most dominant process of reducing [26, 27]. The results of our experiment revealed remarkable reductions in concentrations from between 59.32 and 59.37 mg N/L at the inlet (5cm above soil-water surface) to concentrations below 1 mg N/L at the lower outlet of the soil columns.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al [9] also detected decline in Total-N and nitrate-N concentrations along the wetland but not in the concentrations of ammonium, which may be removed by transient sorption, nitrification, anammox and plant uptake, but also generated through mineralization of organic N, and dissimilatory nitrate reduction to Ammonium [4]. Ackerman et al [41], Maxwell et al [42], and Brauer et al [43] detected significant pollutant reduction along the groundwater flow paths associated with seepage from a wetland. They illustrate that subsurface flux away from wetlands provides another mechanism for N removal.…”
Section: Discussionmentioning
confidence: 99%